Analisis Penggunaan Computer Based Test (CBT) E-Learning Senagai Alternatif Tekhnik Evaluasi Hasil Belajar - Amin, Alfauzan; Nurhasanah, Nurhasanah (Universitas Muhammadiyah Tangerang, 2024)
CBT E-learning is a learning evaluation technique that switches written exams into online-based exams that are carried out using computer devices and internet networks. The purpose of this research is to find out the importance of using CBT E-learning in the process of evaluating learning outcomes in education with Information Technology which is growing rapidly. The research method used in this journal article research is the library method using journals, books and national and international web articles related to Computer Based Test (CBT), E-learning, learning evaluation and CBT utilization in learning evaluation as a source of information. The results of this study are CBT can help educators in compiling more interesting exam questions by including images, videos and audio into the question, CBT also provides an advantage in scoring which is done automatically so as to minimize errors in giving scores, but the application of CBT is not easy, because not all schools have facilities that realize, and CBT requires considerable costs in developing and maintaining the devices and applications used.